2022
DOI: 10.1007/s11192-022-04554-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of acknowledgement texts in Web of Science: a case study on four scientific domains

Abstract: Analysis of acknowledgments is particularly interesting as acknowledgments may give information not only about funding, but they are also able to reveal hidden contributions to authorship and the researcher’s collaboration patterns, context in which research was conducted, and specific aspects of the academic work. The focus of the present research is the analysis of a large sample of acknowledgement texts indexed in the Web of Science (WoS) Core Collection. Record types “article” and “review” from four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Training without the MISC category did not show significant performance progress either. Moreover, further analysis of acknowledged entities showed that the miscellaneous category contained very inhomogeneous and partly irrelevant data, making the analysis more complicated (Smirnova & Mayr, 2023). Therefore, we assume that the model would make better predictions if the number of entity types is expanded and miscellaneous categories excluded, i.e., the MISC category could be split into the following categories: names of projects, names of conferences, names of software and dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training without the MISC category did not show significant performance progress either. Moreover, further analysis of acknowledged entities showed that the miscellaneous category contained very inhomogeneous and partly irrelevant data, making the analysis more complicated (Smirnova & Mayr, 2023). Therefore, we assume that the model would make better predictions if the number of entity types is expanded and miscellaneous categories excluded, i.e., the MISC category could be split into the following categories: names of projects, names of conferences, names of software and dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, no improvement in increasing the size of the corpus for the FUND category can be explained by the ambiguous nature of the entities which fall into the FUND category and their semantical proximity with other types of entities. Analysis of the extracted entities showed that many entities were extracted correctly, but were assigned to the wrong category (Smirnova & Mayr, 2023). Therefore, an additional classification algorithm applied to extracted entities could improve the model's performance.…”
Section: Discussionmentioning
confidence: 99%